Renaissance Florence and the Origins of Capitalism: A Business History Perspective. Issue 1 (2020) - Trivellato, Francesca
Abstract : From the 1940s to the 1970s, the commercial revolution of the Middle Ages was a historiographical concept with considerable traction. This article revisits the literature that brought about and engaged with that concept, with specific reference to Florence. In so doing, it draws attention to the place once held by business history in the study of Europe's takeoff. It also discusses the preliminary results of an ongoing project on limited partnerships in early modern Tuscany, which reaffirms the relevance of business history for understanding preindustrial economies but steers away from a teleological search for the origins of modern capitalism.